Designing Education Game to Choose Hygiene and Healthy Snacks for Children - Vania Wahyu Febriani; T. Brenda Chandrawati; Albertus Dwiyoga Widiantoro (Soegijapranata Catholic University, 2015)
Children from elementary school like to eat snacks or food which are sold by snack sellers around school. Children who like to buy and eat rarely watch the hygiene and healthy of the snacks and the snack sellers which they will buy.Because that habit, the plan of designing education game to educate children is being made. So children can take more attention to choose snack that they will buy. Video games that have theme of hygiene and healthy snacks are rarely can be found.In this paper will be discussed about the habit of children consuming snacks and the design of education game which can be used to educate children based on children habit.